Bioaccessibility and movement of phenolic compounds from tomato (Solanum lycopersicum) during in vitro gastrointestinal digestion and colonic fermentation. Issue 9 (20th April 2022) - Wang, Chuqi; Wu, Hanjing; Liu, Ziyao; Barrow, Colin; Dunshea, Frank; Suleria, Hafiz A. R.
Abstract : Tomato ( Solanum lycopersicum ) is one of the most popular vegetables and has great nutritional values due to the presence of numerous bioactive compounds, especially phenolic compounds. Abstract : Tomatoes ( Solanum lycopersicum ) are highly involved in diets consumed worldwide, and are rich in bioactive compounds including phenolics, carotenoids and vitamins. In this study, four different varieties of fresh tomato pulp (Oxheart, Green Zebra, Kumato and Roma) were used to estimate the bioaccessibility of target phenolic compounds during in vitro gastrointestinal digestion and colonic fermentation, and to determine their antioxidant capacity. The production of short chain fatty acids (SCFAs) was also estimated during colonic fermentation. Among these, Roma displayed relatively higher total phenolic content (TPC) and free radical scavenging (2, 2′-diphenyl-1-picrylhydrazyl (DPPH) assay) values after gastrointestinal digestion of 0.31 mg gallic acid equivalents (GAE) per g and 0.12 mg Trolox equivalents (TE) per g. Kumato exhibited the highest total flavonoid content (TFC) of 2.47 mg quercetin equivalents (QE) per g after 8 hours of colonic fermentation. Oxheart and Roma showed similar ferric reducing antioxidant power (FRAP) values of around 4.30 mg QE per g after 4 hours of faecal reaction. Catechin was the most bioaccessible phenolic compound in all fresh tomatoes, and could be completely decomposed after intestinal digestion, whereas the release of some bonded phenolic compounds required the action of gut microflora. Kumato and Green Zebra showed higher production of individual and total SCFAs for 16 hours of fermentation, which would provide more gut health benefits.